JAMA : The Journal of the American Medical Association (The American Medical Association, 2004)
Contents: preimplantation HLA testing; lipid-lowering therapy and in-hospital mortality following major noncardiac surgery; treatment for cervical intraepithelial neoplasia and risk of preterm delivery; conception for donation;...